Produksi dan Pertumbuhan Ikan Lemuru (Sardinella lemuru) yang Didaratkan di PPI Kedonganan, Bali - Indah Nurtira; I Wayan Restu; Made Ayu Pratiwi (Current Trends in Aquatic Science, 2021)
Lemuru fish resource is one of the fish resources which has important economic value and is of interest to the wider community. Therefore, this resource has been exploited intensively in the Bali Strait and has become the backbone of fishery business activities in the waters. This research was conducted in November-February 2021 at PPI Kedonganan, Bali. This study aims to analyzed the production and growth of Lemuru fish which includes trend analysis and catch composition, growth patterns, length frequency distribution, age groups, and growth parameters of Lemuru Fish. This study found that lemuru fish in PPI Kedonganan had trend an increasing of 99%. Primary data collection in this study, such as measurement of length and weight, was carried out with time intervals of ± 14 days. Lemuru fish that were measured were 600 fish which had a range of 100.2-158.3 mm. Fork lengths ranged from 114.2 to 120.2 mm, consisting of 3 age groups separated by the NORMSEP method using software FISAT II. The shift of the age group to the right 2 times showed that there is growth in the Lemuru fish stock. Based on the length and weight analysis, the results of the analysis of the growth pattern of Lemuru Fish are negative allometric, where the length gain is faster than the weight gain. Lemuru fish has an asymptotic length of 179.6312. This showed that the asymptotic length of Lemuru Fish continues to decrease every year, presumably due topressure overfishing which causes the fish caught to be smaller.